(untitled) (Al-Academy, 2023)
The research aims to identify the extent to which the theatrical and musical arts contribute to diagnosing and treating psychological problems among the residents of children’s villages in Jordan, and the methodologies adopted by the theatrical and musical arts to achieve this. It moves on to prove the theory that theatrical and musical arts have an impact on improving the psychology of the residents of children’s villages in Jordan by reviewing the theories and opinions that address the subject from a scientific point of view proven by experiences and expertise. The research took place in the period between (2019-2020), and the spatial limits came within the (SOS) children’s villages in Jordan. The importance of the research is to provide a frame of reference for researchers and specialists in treating children’s psychological problems using the arts, and the research can benefit those engaged in theatrical and musical art, including authors, directors, actors, critics, composers, singers...etc, as well as providing benefit to academic institutions concerned with theatrical and musical arts and psychological and educational sciences.